The evolution of social media in nephrology education: A mini-review - Shankar, Mythri; Sparks, Matthew A. (Frontiers in Nephrology, 2023)
Social media is defined as “a group of Internet-based applications that build on the ideological and technological foundations of Web 2.0, that allow the creation and exchange of user-generated content”. Social media can be used in medical education to enhance knowledge sharing among peer groups and the public in general. The internet revolutionized learning by allowing easier dissemination of knowledge that did not depend on printing and physical distribution of books, journals, or magazines. According to a report from 2018, 95% of students have access to smartphones and 45% are online at any given time. Social media platforms are powerful tools to spread knowledge by the way of stories, videos, and educational games. Both formal and informal learning can be achieved with the use of social media. The microblogging website Twitter has become a popular social media platform by many in medical education including the nephrology community. Twitter, for example, is used to build communities, discuss journal articles, inform the community of conferences, share infographics and visual abstracts of original research work. As an example, it can be difficult for women in nephrology to connect and travel to make a physical presence. The use of social media allows women to connect via webinars and Women in Nephrology (WIN) India live Twitter chats. Thus, social media can help facilitate networking and collaboration with nephrologists all over the world. Social media has limitations as well. Insensitive posts can have a detrimental effect on one’s career. A survey has shown that increased use of social media can contribute to addiction, anxiety, diminished self-esteem, and even depression. Hence, in order to effectively use social media to contribute positively to one’s career, we recommend considering the positive and negative aspects of social media.This review will discuss the various social media platforms and how they have been applied to nephrology education.